TINGKAT PENGETAHUAN IBU HAMIL TENTANG PENCEGAHAN & PENGOBATAN ANEMIA DEFISIENSI BESI SEBELUM DAN SESUDAH PENYULUHAN DI PMB Bd.I KABUPATEN BANDUNG - Triana, Ayunisa Khofifah; Rahmawati, Naili; Syafrullah, Haidir (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Anemia is a body condition in which the number and size of red blood cells or hemoglobin (Hb) levels are lower than normal, with the WHO classification of anemia in pregnant women, namely, not anemia: 11gr%, mild anemia: 9-10gr%, moderate anemia: 7-8gr%, severe anemia: <7gr%. This study uses a quantitative descriptive research with a population of 30 and a sample of 30 using the accidental sampling technique. From the results of the study, it was found that based on the frequency distribution table the level of knowledge of pregnant women about prevention & treatment of iron deficiency anemia before counseling 11 respondents (36.6%) Good, 19 respondents (63.3%) Enough, and none of the respondents had a low level of knowledge. , The level of knowledge of pregnant women about prevention & treatment of iron deficiency anemia after counseling 20 respondents (66.6%) Good, 10 respondents (33.3%) Enough, and no respondent whose level of knowledge is less Conclusion: Pregnant women are expected to have their pregnancy checked regularly to better understand the condition of their pregnancy, including checking HB, and pregnant women are able to understand how to prevent & treat iron deficiency anemia as early as possible.